The Influence of Financial Literacy, Financial Attitude, and Self-Control on Financial Management Behavior among Students of Slamet Riyadi University - Ginolla Dwika Wijayadi; Alfito Bagas Prasetya; Gita Cahya Aulia; Rusita Nurna Aulia Harun; Rizky Ramadhan Aprian Aditama (Journal of Information System, Applied, Management, Accounting and Research, 2026)
Students' financial independence is rarely tested through major decisions; it is more often revealed in how they handle their everyday small change. This research uses three elements that shape this independence—financial literacy, financial attitude, and self-control—as test variables, then explores the extent to which they shape the financial management behavior of students at the Faculty of Economics and Business, Slamet Riyadi University. A quantitative survey design was applied to 53 selected participants through purposive sampling, using a five-level Likert instrument (score 1 for Strongly Disagree to score 5 for Strongly Agree), and then processed using multiple linear regression on the IBM SPSS Statistics platform. Three main findings emerged from this test. First, financial literacy was shown to contribute a significant unidirectional effect, reflected by a coefficient of 0.384 at a significance level of 0.008. Second, financial attitude showed a similar pattern with a coefficient of 0.365 and a significance level of 0.013. Third, self-control also confirmed its contribution through a coefficient of 0.271 at a significance level of 0.002. When tested together, these three predictors formed a model that explained 61.3 percent of the variation in respondents' financial management behavior (Adjusted R Square = 0.613), a proportion large enough to leave little room for other factors outside the model. The practical implication is clear: financial knowledge needs to be nurtured alongside a healthy attitude and strong self-control, as the three only have their full impact when operating as a package, not as stand-alone elements.